Descemet Membrane Endothelial Keratoplasty for Failed Deep Anterior Lamellar Keratoplasty: A Case Series. Issue 6 (June 2018) - Einan-Lifshitz, Adi; Sorkin, Nir; Boutin, Tanguy; Mednick, Zale; Kreimei, Mohammad; Chan, Clara C.; Rootman, David S.
Abstract : Purpose: To suggest a new surgical approach for posterior opacities or persistent Descemet membrane (DM) detachment in failed deep anterior lamellar keratoplasty (DALK) and to report the outcome of Descemet membrane endothelial keratoplasty (DMEK) in a series of patients with DALK failure. Methods: In this retrospective case series of patients who underwent DMEK for failed DALK at Toronto Western Hospital, 4 patients with failed DALK who underwent DMEK surgery were included. In all 4 cases, big bubble formation during initial DALK surgery had failed and the surgical technique was converted to manual dissection using the Melles technique. In 2 cases, the descemetorhexis in DMEK surgery was performed manually, and in 2 cases, the descemetorhexis was performed with the assistance of the femtosecond laser. Results: Four eyes of 4 patients aged 70 ± 4 years were included. Average follow-up time was 9 ± 5 months. Indications for DALK surgery were corneal dystrophy in 2 patients and corneal scars in the other 2. DALK failure was due to persistent DM detachment that created a double chamber in 2 patients and due to posterior lamellar haze in the other 2. After DMEK surgery, 2 patients had graft detachment and required rebubbling. In 1 patient, the DMEK scroll was attached after 1 rebubble attempt, and in the other patient, a second rebubble attempt was needed. The final visual acuities were 20/40, 20/50, 20/70, and 20/200 (because of dense cataract). All procedures were uneventful. Conclusions: DMEK surgery may be effective in managing DALK failure.